2017
DOI: 10.4103/pm.pm_358_16
|View full text |Cite
|
Sign up to set email alerts
|

Constituents and antioxidant activity of bleeding sap from various Xinjiang grapes

Abstract: Objective:Wine grape sap or bleeding sap of grapes (GBS) is commonly used in Xinjiang (China) for therapeutic aims. Do variations in composition related to region and variety affect its properties?Methods:GBS samples originating in various parts of Xinjiang (Turpan, Hotan, Kashgar, and Atush) were tested for phenols and polyphenols, polysaccharides, saponin, proteins, individual amino acids, and minerals. Their antioxidant activity was measured using ascorbic acid as reference.Results:Polyphenol content varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The unfractionated FGSCExt contained many different elements with very high levels of potassium (K) and calcium (Ca). Le et al (2017) also reported high levels of these two compounds from the "bleeding sap of grapes".…”
Section: Chemical Properties Of Fgp Elemental Analysismentioning
confidence: 95%
“…The unfractionated FGSCExt contained many different elements with very high levels of potassium (K) and calcium (Ca). Le et al (2017) also reported high levels of these two compounds from the "bleeding sap of grapes".…”
Section: Chemical Properties Of Fgp Elemental Analysismentioning
confidence: 95%
“…In addition, bleeding can lead to nutrient loss and induced plant bleeding sap canker disease [17,18]. However, bleeding sap contains a large number of bene cial substances, so bleeding sap is widely used as medical product [19,20]. A lot of plant species can secretion bleeding sap after bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bleeding can lead to nutrient losses and is capable of inducing the onset of plant bleeding sap canker disease [ 19 , 20 ]. Intriguingly, there are no obvious plant fitness benefits to bleeding on a branch; however, bleeding sap contains a large number of beneficial substances, so bleeding sap is widely collected and used as medical product [ 21 , 22 ]. Many plant species can secretion bleeding sap after bleeding.…”
Section: Introductionmentioning
confidence: 99%